A volitional account of aesthetic experience - McCrae, Robert R. (Frontiers in Psychology, 2024)
Aesthetic experience is an altered state of consciousness characterized by a detached absorption in an aesthetic object; it is a pleasant—sometimes ecstatic—liberation from the self and its agenda. I briefly review perceptual-cognitive and affective approaches used by psychologists to understand the phenomenon and suggest the need for a volitional perspective. To illustrate the nature and scope of aesthetic experience, I discuss nine varieties, elicited by different qualities in objects and evoking distinctive responses in perceivers. Over centuries, aesthetic devices have been developed that induce the aesthetic state by manipulating such psychological mechanisms as attention, appraisal, and empathy. I propose explanations for how several important devices operate, and why they are particularly effective in individuals high in the personality trait of Openness to Experience.